Rozwój metod ilościowych w bankowości - Siarka, Paweł (Development of quantitative methods in banking, 2011)
Over the past two decades we have seen many changes in the banking world due to the development of the banking market and also due to the development of quantitative methods, which allow us to estimate the level of banking risks with greater accuracy. Mathematical models, which are developed by teams of analysts and then implemented in the banking systems, are evidence of practical application of mathematics in finance. Implemented by leading banks in the world, mathematical models set the direction of development of risk management process for the entire banking industry. These achievements are the subject of ongoing research by the Basel Committee, whose recommendations create global banking standards. Over the last twenty years, the Basel Committee has recommended several methods of risk analysis to protect the world banking system. In this article the author focuses on the analysis of credit risk, which evolved in cooperation with the Basel Committee. Thus, some suggestions are presented with respect to teaching banking risks in the context of knowledge of quantitative methods
Didactics of Mathematics, 2011, Nr 8 (12), s. 127-134
Keywords: Basel II; risk management; one factor model; credit risk